Penguatan Kesadaran Berkoperasi Dan Pentingnya Membangun Kecerdasan Finansial Anggota Credit Union Tirta Dana Surabaya - Lena Ellitan; Dominicus Wahyu Pradana; Ninuk Muljani (LPPM, Universitas Katolik Widya Mandala Surabaya, 2021)
Cooperative education, especially by the Indonesian people, including members of the Tirta Dana Credit Union, aims to increase understanding of the cooperative concept and how to become a member wisely and have a role in it. Education on financial management for members is considered necessary and provides opportunities to learn the basics related to income, expenses, savings, and loans. This PkM activity is a coaching effort that is expected to help members of Credit Union Tirta Dana in formulating dreams of welfare and building members' financial health. This activity is the main goal of the UKWMS Management Study Program in an effort to play a role in developing financial intelligence for Tirta Dana Credit Union members, especially in contributing to the creation of greater value to the community